Probiotics and Vitamin D/Vitamin D Receptor Pathway Interaction: Potential Therapeutic Implications in Inflammatory Bowel Disease - Pagnini, Cristiano; Di Paolo, Maria Carla; Graziani, Maria Giovanna; Delle Fave, Gianfranco (Frontiers in Pharmacology, 2021)
Inflammatory bowel diseases (IBD) are chronic conditions of unknown etiology and immunomediated pathogenesis. In the last years, the comprehension of the complex mechanisms involved in the intestinal mucosal homeostasis has been consistently enriched. Specifically, the extraordinary impulse in the field of research of the intestinal microbiome has opened the door to the investigation of possible novel approaches to the diagnosis, management and therapeutic applications in IBD. In line with that, administration of probiotic bacteria has been intensely evaluated, but with much more exciting results in experimental models than in clinical practice. Considering the consistent heterogeneity of the available studies about probiotics, the increased knowledge of the properties of the single bacterial species would ideally lead to unravel potential mechanisms of action that may bring therapeutic application in specific pathologic condition. Among the relevant molecular pathways for mucosal homeostasis maintenance, the vitamin D/vitamin D receptor (VDR) pathway has been intensely studied in the very last years. In fact, besides osteometabolic functions, the vitamin D exerts important homeostatic effects in the organism at multiple levels, such as immunomodulation, inflammation control, and microbiota regulation, which are likely to play relevant role in intestinal mucosa protection. In the present review, recent findings about probiotic applications in IBD and mechanisms of action linking vitamin D/VDR pathway to IBD are reported. Available evidence for probiotic effect on vitamin D/VDR are reviewed and potential future application in IBD patients are discussed. Microbiota manipulation and vitamin/VDR pathway appear a promising field for future research and therapeutic developments.